2020
DOI: 10.1186/s12875-020-1083-8
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction, burnout, and turnover intention among primary care providers in rural China: results from structural equation modeling

Abstract: Background Low job satisfaction, severe burnout and high turnover intention are found to be prevalent among the primary care providers (PCPs) in township health centers (THCs), but their associations have received scant attention in the literature. In light of this, this study aims to examine the relationships between job satisfaction, burnout and turnover intention, and explore the predictors of turnover intention with a view to retaining PCPs in rural China. Methods Using the multistage cluster sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 36 publications
10
112
0
8
Order By: Relevance
“…The results showed that primary care providers were generally dissatisfied with their financial situation. This finding was consistent with a previous study that found primary care providers were the least satisfied with their income [ 38 ]. Since 1980, primary care providers in China have been able to charge a 15% markup on drug sales, but this was abolished in 2017 because of over-prescribing of drugs.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that primary care providers were generally dissatisfied with their financial situation. This finding was consistent with a previous study that found primary care providers were the least satisfied with their income [ 38 ]. Since 1980, primary care providers in China have been able to charge a 15% markup on drug sales, but this was abolished in 2017 because of over-prescribing of drugs.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that primary care providers were generally dissatis ed with their nancial situation. This nding was consistent with a previous study that found primary care providers were the least satis ed with their income [33]. Since 1980, primary care providers in China have been able to charge a 15% markup on drug sales, but this was abolished in 2017 because of over-prescribing of drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Although these studies indicate an increased prevalence of burnout [21][22][23], they are limited as they mostly focus on a specific setting (e.g. township health centres representing rural areas or community health centres representing urban areas) [21,22,24,25] or on regional (e.g. city or provincial level) contexts [19,26,27]; these studies pay little attention to different types of PC providers and define PC providers by their job category as opposed to their type of service provision.…”
Section: Introductionmentioning
confidence: 99%